The Role of FOMO, Personalization, and Social Sharing in Driving Customer Engagement and Brand Loyalty: Insights from Spotify Wrapped in Indonesia - Agung Stefanus Kembau; Fresi Beatrix Lendo; Antonius Felix; Youngky Vincent (Universitas Bunda Mulia, 2024)
This study investigates the roles of Fear of Missing Out (FOMO), personalization, and social sharing behavior in influencing customer engagement and brand loyalty, with social media activity as a moderating factor. Using Spotify Wrapped as a case study, data was collected from 205 active Spotify users in Indonesia through an online survey. Structural Equation Modeling (SEM) was employed to analyze the relationships between variables and test the moderating effect. The findings show that personalization is the strongest driver of customer engagement, followed by social sharing behavior and FOMO. Social media activity significantly amplifies the effect of FOMO on engagement, highlighting the critical role of Indonesia’s highly social and trend-driven digital culture. Additionally, customer engagement strongly mediates the relationship between these factors and brand loyalty, underscoring the importance of emotional connections in retaining users. This study contributes to understanding how digital engagement strategies, such as Spotify Wrapped, resonate in culturally specific contexts like Indonesia. The results provide actionable insights for marketers and digital platforms aiming to leverage personalization and social influence to enhance user engagement and loyalty, while acknowledging the need for further exploration in diverse markets.Penelitian ini mengkaji peran Fear of Missing Out (FOMO), personalisasi, dan perilaku berbagi di media sosial dalam memengaruhi keterlibatan pelanggan (customer engagement) dan loyalitas merek (brand loyalty), dengan aktivitas media sosial sebagai variabel moderasi. Menggunakan Spotify Wrapped sebagai studi kasus, data dikumpulkan dari 205 pengguna aktif Spotify di Indonesia melalui survei online. Analisis dilakukan menggunakan Structural Equation Modeling (SEM) untuk menguji hubungan antar variabel dan efek moderasi. Hasil penelitian menunjukkan bahwa personalisasi merupakan faktor terkuat yang mendorong keterlibatan pelanggan, diikuti oleh perilaku berbagi di media sosial dan FOMO. Aktivitas media sosial secara signifikan memperkuat efek FOMO terhadap keterlibatan, yang menyoroti peran penting budaya digital Indonesia yang sangat sosial dan berorientasi pada tren. Selain itu, keterlibatan pelanggan secara kuat memediasi hubungan antara faktor-faktor tersebut dengan loyalitas merek, menegaskan pentingnya koneksi emosional dalam mempertahankan pelanggan.Penelitian ini berkontribusi pada pemahaman tentang bagaimana strategi keterlibatan digital, seperti Spotify Wrapped, beresonansi dalam konteks budaya spesifik seperti Indonesia. Temuan ini memberikan wawasan praktis bagi pemasar dan platform digital untuk memanfaatkan personalisasi dan pengaruh sosial dalam meningkatkan keterlibatan dan loyalitas pengguna, dengan tetap mengakui perlunya eksplorasi lebih lanjut di pasar yang beragam